2019
DOI: 10.1002/cnma.201900010
|View full text |Cite
|
Sign up to set email alerts
|

Doping and Photon Induced Defect Healing of Hybrid Perovskite Thin Films: An Approach Towards Efficient Light Emitting Diodes

Abstract: Here, we demonstrate a simple method to improve photoluminescence and electroluminescent properties of MAPbBr3 perovskite thin films by monovalent Cs cation doping and treatment with UV light. It is known that the intermediate species of lead halides, which limits the photoluminescence quantum yield (PLQY) of perovskite thin films, are formed due to the presence of an organic polar solvent. In such cases, coalescence of nanocrystals is unavoidable when the thin‐films are thermally annealed to remove the interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In particular, the stability of perovskite devices has been associated with moisture/heat instability of the A-site organic cation in the ABX3 perovskite crystal structure (where A is a monovalent cation (methylammonium (MA + ), formamidinium (FA + ) or cesium (Cs + )), B is a divalent cation (Pb 2+ , Mn 2+ or Zn 2+ ), and X is a halide anion (I -, Bror Cl -)), joule heating at operational bias, and halide ion migration. [9][10][11][12][13][14][15][16][17][18] Numerous approaches have been employed to remove joule heating by using thermally stable materials and to suppress ion migration by doping or mixing with poly(ethylene oxide) (PEO), 19,20 phenylethylammonium (PEA), 21 (9,9-bis(3-(N,Ndimethylamino)propyl)-2,7-fluorene)-alt-2,7-(9,9-dioctylfluorene) (PFN), 22 and 3,3diphenylpropylamine bromide (DPPA-Br), 23,24 . Additionally, improving structural stability by substitution or doping of A-(MA + , FA + , Cs + ), and B-(Pb 2+ , Mn 2+ , Zn 2+ , Ce 3+ ) site cations have been explored.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the stability of perovskite devices has been associated with moisture/heat instability of the A-site organic cation in the ABX3 perovskite crystal structure (where A is a monovalent cation (methylammonium (MA + ), formamidinium (FA + ) or cesium (Cs + )), B is a divalent cation (Pb 2+ , Mn 2+ or Zn 2+ ), and X is a halide anion (I -, Bror Cl -)), joule heating at operational bias, and halide ion migration. [9][10][11][12][13][14][15][16][17][18] Numerous approaches have been employed to remove joule heating by using thermally stable materials and to suppress ion migration by doping or mixing with poly(ethylene oxide) (PEO), 19,20 phenylethylammonium (PEA), 21 (9,9-bis(3-(N,Ndimethylamino)propyl)-2,7-fluorene)-alt-2,7-(9,9-dioctylfluorene) (PFN), 22 and 3,3diphenylpropylamine bromide (DPPA-Br), 23,24 . Additionally, improving structural stability by substitution or doping of A-(MA + , FA + , Cs + ), and B-(Pb 2+ , Mn 2+ , Zn 2+ , Ce 3+ ) site cations have been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, improving structural stability by substitution or doping of A-(MA + , FA + , Cs + ), and B-(Pb 2+ , Mn 2+ , Zn 2+ , Ce 3+ ) site cations have been explored. [10][11][12][13][14][15][16][17][18] Various efforts have also been made in tuning the dimensionality of the perovskite by substituting the A-site cations with organic additives and long chain ammonium salts such as alkyl ammonium, 25 phenylethylammonium, [26][27][28][29] 1naphthylmethylammonium, [30][31][32] and phenylbutylammonium 33 to improve the device performance. All-inorganic perovskites, having higher decomposition temperatures, also benefit from higher operational stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various perovskite components, MAPbBr 3 has great potential for preparing high-efficiency Pero-LEDs. However, it is reported that the most primitive perovskite films comprising MAPbBr 3 (i.e., PbBr 2 :MABr = 1:1) exhibit low surface coverage, poor structural stability, and poor crystalline quality with too many nonradiative defects [24,25]. To improve the film quality of MAPbBr 3 perovskite, Lee et al precisely adjusted the molar proportion of MABr and PbBr 2 [4].…”
Section: Introductionmentioning
confidence: 99%